PENGARUH PURSED LIP BREATHING TERHADAP SATURASI OKSIGEN PADA PASIEN POST GENERAL ANESTHESIA DI RUANG BEDAH RS LAVALETTE KOTA MALANG - Dimas Bagus Kurniawan; susi milwati; naya ernawati (Poltekkes Kemenkes Malang, 2022)
Postoperative patients with general anesthesia who experience complications In the respiratory system, respiratory depression is found to be associated with decreased oxygen saturation. The Pursed Lip Breathing exercise is a non-pharmacological action aimed at facilitating the process of removing air trapped by the airways in an effort to increase the value of oxygen saturation. The purpose of this study was to see the effect of Pursed Lip Breathing on oxygen saturation in post general anesthesia patients. This study used Quasy-experiment With Pretest Posttest Control Group Desaign. The sampling used in this study was a non-probability sampling type of purposive sampling with 30 respondents divided into 15 control groups and 15 treatment groups. The test used in this study was to examine the differences between pre and post, intervention groups and control groups using the Wiloxon test then to compare the results of the post-intervention group and Post group control groups using the independent Mann Whitney test. The results showed a p value of 0.039 (p value less than 0.05) in the pre and post control group and in the treatment group p-value 0.001 (p value less than 0.05) This shows that the pre and post oxygen saturation values in the two groups differed while the post-test difference in the control and treatment groups was 0.015 (p value less than 0.05), so there was a difference in oxygen saturation in patients given general anesthesia and not used pursued lip breathing. Thus the pursed lip breathing has an influence on oxygen saturation in patients with post general anethesia.The next recommendation is the relationship of the value of carbon dioxide (CO2) levels that can affect the value of oxygen saturation.